Distribution and health risk assessment of trace metals in freshwater tilapia from three different aquaculture sites in Jelebu Region (Malaysia). (15th June 2015) - Low, Kah Hin; Zain, Sharifuddin Md.; Abas, Mhd. Radzi; Md. Salleh, Kaharudin; Teo, Yin Yin
Highlights: We examined heavy metal levels in red tilapias from freshwater aquaculture sites. They were below the prescribed limits except for As and Cd from ex-tin mining pool. The carcinogenic risk of inorganic As at the 95th percentile could be of concern. Considerable As content is plausibly due to utilization of metal-enriched feeds. Abstract: The trace metal concentrations in edible muscle of red tilapia ( Oreochromis spp.) sampled from a former tin mining pool, concrete tank and earthen pond in Jelebu were analysed with microwave assisted digestion-inductively coupled plasma-mass spectrometry. Results were compared with established legal limits and the daily ingestion exposures simulated using the Monte Carlo algorithm for potential health risks. Among the metals investigated, arsenic was found to be the key contaminant, which may have arisen from the use of formulated feeding pellets. Although the risks of toxicity associated with consumption of red tilapia from the sites investigated were found to be within the tolerable range, the preliminary probabilistic estimation of As cancer risk shows that the 95th percentile risk level surpassed the benchmark level of 10 −5 . In general, the probabilistic health risks associated with ingestion of red tilapia can be ranked as follows: former tin mining pool > concrete tank > earthen pond.